Imidazolium dihydrogenphosphate - C. B. Jasciezek, U of Sussex, UK (My University, 2017)
Inelastic Neutron Scattering spectrum of Imidazolium dihydrogenphosphate, C₃H₇N₂PO₄, measured on the TFXA instrument.
Keywords: TFXA